التنظيم القانوني لمهلة الانتظار في مشارطة إيجار السفينة المجهزة بالرحلة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يلتزم المؤجر في مشارطة إيجار السفينة المجهزة بالرحلة أن يتيح السفينة لأعمال الشحن و التفريغ التي يتوجب على المستأجر إنجازها خلال فترة زمنية يحددها الاتفاق أو العرف تسمى مهلة الانتظار لا يدفع عنها المستأجر أي أجرة إضافية لأنها تعتبر مدفوعة الأجر ضمناً في الأجرة المتفق عليها في المشارطة، فإذا تأخر المستأجر و تجاوز مهلة الانتظار سرت مهلة إضافية يستحق عنها المؤجر أجرة إضافية يحددها الاتفاق أو العرف، بالمقابل وكتحفيز للمستأجر لإنجاز أعمال الشحن و التفريغ في أسرع وقت ممكن قد تتضمن المشارطة شرطاً بدفع مكافأة للمستأجر عن الوقت المختصر من مهلة الانتظار. The shipowner in the voyage charterparty is under an obligation to make and keep the vessel available for loading and discharging operations and the charterer is bound to perform these operations during a certain period of time specified by the parties agreement or according to the custom, such a period is known as Laytime and it is  available free of charge to the charterer who is regarded as having paid for it in the freight. However, If the charterer exceed the laytime and delayed the vessel beyond it, then an extra period starts to run with additional amount specified by the parties agreement or according to the custom is payable to the owner known as Demurrage. In the other hand as an inducement to the charterer to complete the loading and discharging operations as quickly as possible, the charter may provide for a reward to the charterer known as despatch money for any laytime saved.